Reaction-in-Flight neutrons as a test of stopping power in degenerate plasmas. (May 2016) - Hayes, A C; Cerjan, C J; Jungman, G; Fowler, M M; Gooden, M E; Grim, G P; Henry, E; Rundberg, R S; Sepke, S M; Schneider, D H G; Singleton, R L; Tonchev, A P; et al.
Abstract: Cryogenically cooled inertial confinement fusion capsule designs are suitable for studies of reaction-in-flight (RIF) neutrons. RIF neutrons occur when energetically up-scattered ions undergo DT reactions with a thermal ion in the plasma, producing neutrons in the energy range 9-30 MeV. The knock-on ions lose energy as they traverse the plasma, which directly affects the spectrum of the produced RIF neutrons. Here we present measurements from the National Ignition Facility (NIF) of RIF neutrons produced in cryogenic capsules, with energies above 15 MeV. We show that the measured RIFs probe stopping under previously unexplored degenerate plasma conditions and constrain stopping models in warm dense plasma conditions.